Judging in rhythmic gymnastics at different levels of performance - Leandro, C.; Avila-Carvalho, L.; Sierra-Palmeiro, E.; Bobo-Arce, M. (Journal of Human Kinetics, 2017)
This study aimed to analyse the quality of difficulty judging in rhythmic gymnastics, at different levels of performance. The sample consisted of 1152 difficulty scores concerning 288 individual routines, performed in the World Championships in 2013. The data were analysed using the mean absolute judge deviation from the final difficulty score, a Cronbach`s alpha coefficient and intra-class correlations, for consistency and reliability assessment. For validity assessment, mean deviations of judges` difficulty scores, the Kendall`s coefficient of concordance W and ANOVA eta-squared values were calculated. Overall, the results in terms of consistency (Cronbach`s alpha mostly above 0.90) and reliability (intra-class correlations for single and average measures above 0.70 and 0.90, respectively) were satisfactory, in the first and third parts of the ranking on all apparatus. The medium level gymnasts, those in the second part of the ranking, had inferior reliability indices and highest score dispersion. In this part, the minimum of corrected item-total correlation of individual judges was 0.55, with most values well below, and the matrix for between-judge correlations identified remarkable inferior correlations. These findings suggest that the quality of difficulty judging in rhythmic gymnastics may be compromised at certain levels of performance. In future, special attention should be paid to the judging analysis of the medium level gymnasts, as well as the Code of Points applicability at this level.